Thermodynamic analysis and operation investigation of a cross-border integrated energy system based on steam Carnot battery. (5th February 2023) - Lin, Xiaojie; Sun, Peng; Zhong, Wei; Wang, Jian
Highlights: Design a novel steam Carnot battery based on phase change materials. Steam Carnot battery realizes electricity-steam complementation for industrial parks. Analyze steam Carnot battery's performance in integrated energy system scenario. Steam Carnot battery is promising for cross-border integrated energy system. Abstract: With the booming development of industrial parks in southern Belt and Road (B&R) countries, the demand for energy carriers such as electricity and steam grows rapidly. One key aspect of B&R initiative is to promote cross-border energy cooperation in these countries. However, this region has abundant renewable energy resources, while the electricity and steam supply required in industrial processes is insufficient. This paper proposes a cross-border integrated energy system (IES) based on Carnot battery technology. A steam Carnot battery (SCB) is designed based on phase change material with water/steam as the working fluid. This paper establishes thermodynamic model of the proposed IES and evaluates its performance. Based on a field investigation in a real cross-border China-Myanmar industrial park, this paper designs the corresponding IES and studies SCB's impact on IES daily operation. A baseline IES having an electric battery is also proposed to facilitate the comparison. The result shows that IES based on SCB reduces 28.57% operating cost, 43.49% carbon emission, and 16.49% city grid electricity consumption compared with the baseline. This means electro-thermal complementarity is an essential feature of SCB in IES. Furthermore, shadow price approach is adopted to analyze the impact of SCB in IES with the development of the industrial park. Renewable electricity output and peak-valley ratio have high shadow prices. The operating cost of IES based on SCB is highly affected by the percentage of renewable energy introduction and pricing market, making it a promising choice in this region known for redundant hydropower. Although electricity storage capacity and SCB's roundtrip efficiency have less impact on cost reduction, they can reduce carbon emission for IES. This study provides a new perspective for constructing the energy system in B&R initiative areas.